Consolidated bioprocessing for sodium gluconate production from cellulose using Penicillium oxalicum. (March 2018) - Han, Xiaolong; Liu, Guodong; Pan, Yunjun; Song, Wenxia; Qu, Yinbo
Graphical abstract: Highlights: Penicillium oxalicum z19 co-overexpressed GOD and CAT from Aspergillus niger . Two-stage temperature control strategy was applied for sodium gluconate production. 13.54 g/L sodium gluconate was obtained from cellulose in one-pot reaction. Abstract: The feasibility of consolidated bioprocessing for sodium gluconate production from cellulose was studied. A recombinant strain named z19 was constructed from Penicillium oxalicum wild-type strain 114-2 for simultaneous expression of glucose oxidase and catalase from Aspergillus niger . While keeping a cellulolytic ability similar with that of 114-2, z19 secreted certain amounts of glucose oxidase and catalase. Fed-batch and two-stage temperature control strategy (0–120 h, 30 °C; 120–192 h, 45 °C) was utilized for sodium gluconate production from cellulose (filter paper power), with 13.54 g/L of sodium gluconate obtained at the end of the fermentation. The results provide an alternative route for producing sodium gluconate from cellulose in a one-pot reaction.